PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS IV DI SDN BONDONGAN - Septiani Dinila, Hana; Siti Sundari, Fitri; Nurjanah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of variety of approaches, methods and media used in the learning process causes learning activities to tend to be conventional and teacher-centered so that the lack of student motivation in learning Indonesian. This study aims to apply the Culturally Responsive Teaching (CRT) approach with wordwall media to increase the learning motivation of fourth grade students of SDN Bondongan. The research method used was Classroom Action Research (PTK) which was carried out with two cycles. The research subjects were all fourth grade students at SDN Bondongan, totaling 27 students. Research data obtained through observation and questionnaire. The data analysis technique used in this research is descriptive qualitative. Based on the research, it shows that the application of the CRT approach assisted by wordwall media can increase student learning motivation by 15.59% from pre-cycle 65.43% in the sufficient category to 81.02% in cycle I with a good category. The increase from cycle I to cycle II was 10.03% to 91.05% with a very good category. based on data analysis, it can be concluded that the application of the CRT approach with wordwall media can increase the learning motivation of fourth grade students of SDN Bondongan in Indonesian language learning.